Expansion Of Value And Form Dol Musicality As Ritual Tabot In Bengkulu - Bambang Parmadie; I Gede Arya Sugiartha (Institut Seni Indonesia Denpasar, 2018)
The expansion of value and form musicality in Tabot ritual music includes ideology, musicality and new sociocultural phenomena in the performing arts extend to all elements of Bengkulu society in general. The sacred music referred to in the Tabot rituals of Bengkulu is Dol music. The transformations in forms of Dol music and musicality are: sacred musicality becomes secular or profane. The physical form, function, and aesthetic of Dol music in Tabot rituals have an ever-increasing creativity in their development, musical progress and sociocultural-supporter progress. The commodification of Dol music transforms the artistic identity associated with new music from Bengkulu. The development of musicality moves freely, making changes in sacred ideology. This analysis reveals problems using social practice theory, hegemonic theory, and popular culture theory, applied eclectically by using a qualitative method. Data is collected Through observation, interview, and document study. The findings of this research are that there are forms of exploration and exploitation of Dol music from sacred to secular or profane and vice versa in the context of the commodification of physical musicality, function, and aesthetics in the ideological identity of the supporting community and the musical space dimension. The secular or profane Dol music permeates and indoctrinates the sacred Dol musical ideology as the musical ceremony of Tabot ritual. The counter-assumption about a sacred art form that will experience a shift into secular or profane is not entirely true for Dol music in Bengkulu.